1999
DOI: 10.1002/(sici)1099-1085(199907)13:10<1511::aid-hyp828>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of nutrient concentration in the groundwater of a floodplain: effect of hydrology, vegetation and substrate

Abstract: Abstract:Spatio-temporal variations in nitrogen and phosphorus concentrations in groundwater were analysed and related to the variations in hydrological conditions, vegetation type and substrate in an alluvial ecosystem. This study was conducted in the Illwald forest in the Rhine Plain (eastern France) to assess the removal of nutrients from groundwater in a regularly¯ooded area. We compared both forest and meadow ecosystems on clayey-silty soils with an anoxic horizon ( pseudogley) at 1 . 5±2 m depth (eutric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
2
31
0
1
Order By: Relevance
“…This suggests that the P in the groundwater system originates from the riparian zone surface and surface soil, rather than from the adjacent agricultural fields. Previous studies have shown that high water tables in riparian zones can cause leaching of decayed vegetation (Takatert et al, 1999), which increases concentrations of particulate organic P in groundwater. At this site, groundwater subsequently migrates into the Beverly Swamp, south of the research site.…”
Section: Riparian Zone Hydrologymentioning
confidence: 99%
“…This suggests that the P in the groundwater system originates from the riparian zone surface and surface soil, rather than from the adjacent agricultural fields. Previous studies have shown that high water tables in riparian zones can cause leaching of decayed vegetation (Takatert et al, 1999), which increases concentrations of particulate organic P in groundwater. At this site, groundwater subsequently migrates into the Beverly Swamp, south of the research site.…”
Section: Riparian Zone Hydrologymentioning
confidence: 99%
“…The reduction of phosphorus concentrations in groundwater by riparian forests has usually been attributed to root absorption (Sánchez-Pérez et al 1991a), chemical precipitation and adsorption processes (Reddy and Rao 1983;Patrick 1990). Some other studies have documented the effects of factors as well as the interactions which regulate the transfer of nutrients to groundwater, for example geomorphology (Pinay et al 1995), catchment hydrology (Cooper 1990) and vegetation type (Takatert et al, 1999;Sánchez-Pérez and Trémolières, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have indicated that the woodland in the riparian zone could effectively remove nutrients from the upland (Cey et al, 1999;Takatert et al, 1999;Clement et al, 2003). In our research, the woodlands were located at the lower slope of the croplands.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, during the developing process of the ephemeral stream from incised gully, cracks created by many stones with different sizes in the stream bed favored the water and nitrogen transport from the upland. When ammonium-N in shallow groundwater reached woodland, the anoxic environment created by high groundwater table was favorable to the existence of ammonium-N, as shown by other researchers (Takatert et al, 1999;Clement et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation